2014
DOI: 10.1155/2014/530687
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Chloride: Can It Be a New Treatment Option for Ulcerative Colitis?

Abstract: Background/Aims. Patients with ulcerative colitis still need effective therapy without major side effects. It has been found that strontium can suppress NFκB activation induced by TNF-α. This opens a gate to a new anti-TNF agent which is cheap and can be given orally. We for the first time aimed to investigate the effect of strontium chloride (SrCl2) on inflammation in experimental colitis. Methods. Thirty female Wistar albino rats were divided into 5 groups each containing 6 rats. The rats in groups 1 and 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…(14) We have planned this study in the light of all this information, we investigated the effect of SR and HPE on inflammation in experimental colitis and compared it with a novel therapeutic agent prednisolone. In our histopathological results, we observed that SR was effective in the cure of colitis, as in Firdevs et al (7). On the other hand, oral application of HPE has been shown to exacerbate inflammation in the colon segments.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…(14) We have planned this study in the light of all this information, we investigated the effect of SR and HPE on inflammation in experimental colitis and compared it with a novel therapeutic agent prednisolone. In our histopathological results, we observed that SR was effective in the cure of colitis, as in Firdevs et al (7). On the other hand, oral application of HPE has been shown to exacerbate inflammation in the colon segments.…”
Section: Discussionsupporting
confidence: 83%
“…It has also been shown that human monocytes perform inflammatory mediator production by suppressing NF-[kappa] B activation (19). In a similar study, Fırdevs T et al (7) found that that strontium chloride has comparable therapeutic efficiency with prednisolone in rat colitis model.…”
Section: Discussionmentioning
confidence: 92%
“…In mice, for example, sodium arsenite was associated with a reduction in the severity of DSS-induced experimental colitis 49 and arsenic trioxide had anti-inflammatory consequences in TNBS-induced colitis 50 . Likewise, preclinical studies using cobalt 51 , lithium 52 , strontium 53 and uranium 54 also found a clear anti-inflammatory potential. Lastly, some preliminary data strongly suggest that mice exposed to methylmercury for 3 weeks are resistant to DSS-associated inflammation (Body-Malapel and Vignal, unpublished data).…”
Section: Discussionmentioning
confidence: 91%
“…Таким образом, показана способность стронция влиять на важнейшие показатели иммунной регуляции у детского населения при повышенном содержании металла в источниках питьевого водоснабжения. Данные литературы также подтверждают возможность функциональных изменений иммунной реактивности под воздействием стронция [5,6,10]. В нашем исследовании у обследованной группы детского населения выявлены существенные сдвиги параметров как гуморального, так и клеточного звена иммунитета на фоне повышения специфической сенсибилизации к металлу, а также нарушение процесса запуска и регуляции апоптоза.…”
Section: заключениеunclassified